2010
DOI: 10.1002/jobm.201000160
|View full text |Cite
|
Sign up to set email alerts
|

High Archaea diversity in Varvara hot spring, Bulgaria

Abstract: The phylogeny of the latest recognized domain, Archaea, is still complicated and it is largely based on environmental sequences. A culture independent molecular phylogenetic analysis revealed high Archaea diversity in a terrestrial hot spring, village Varvara, Bulgaria. A total of 35 archaeal operational taxonomic units (OTUs) belonging to three of the classified five Archaea phyla were identified. Most of the sequences were affiliated with the phylum Crenarchaeota (23), grouped in four branches. The rest of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
1
Order By: Relevance
“…However, 99 % of the Acidithiobacillus-sequences were 99 % identical to Acidithiobacillus caldus. This is in contrast to the majority of other environmental studies, in which the largest proportion of sequences does not affiliate with cultivated species Ivanova et al 2011;Pagaling et al 2012).…”
Section: Dominant Metabolic Pathways In the Hot Springs Of Furnascontrasting
confidence: 95%
“…However, 99 % of the Acidithiobacillus-sequences were 99 % identical to Acidithiobacillus caldus. This is in contrast to the majority of other environmental studies, in which the largest proportion of sequences does not affiliate with cultivated species Ivanova et al 2011;Pagaling et al 2012).…”
Section: Dominant Metabolic Pathways In the Hot Springs Of Furnascontrasting
confidence: 95%
“…our recent studies demonstrated that hot springs in Bulgaria are inhabited by thermophilic microbial communities of rich biodiversity, suitable as a source for sequence-based cloning of novel genes encoding thermostabile proteins, (2,11,26). During our research on sequence-based metagenomic cloning of new genes from glycosyl hydrolase families Gh13 and Gh57 retrieved from hot spring DnA samples and their following expression in B. megaterium, we encountered several problems related to the needs of multiple cloning in expression vectors, as well as, multiple gene fusion cloning and characterization of the enzyme activity and thermal stability of the expressed recombinant proteins.…”
Section: Introductionmentioning
confidence: 99%
“…the expanding of the available sequence data on polysaccharide modifying enzymes and genes make possible the including of metagenomic analysis of such genes in parallel with rRnA gene analysis, in complex characterization of environmental microbial biodiversity. VLASA HOT SPRING, BULGARIA, BY USING 16S RRNA AND GLYCOSIDE HYDROLASE FAMILY 4 GENES TABLE 1 Sequences of the primers used for PCR amplification of fragments from GH4 gene Primer name Primer sequence Amino acid sequence of the corresponding GH4 conserved region GF1G 5'-aaaaagcaggctaayagygtkgaatggaayatggt nSVeWnM GF2G 5'-aaaaagcaggctvayacnatntggggntaytayca xtXWGYY GR1G 5'-agaaagctgggtgtytyragryyccartgtayttcca WKYxGxxx GR2G 5'-agaaagctgggtcgrccrccrcccagraabgc AFlGGG in our recent 16S rRnA gene study on the environmental samples from Varvara hot spring, Velingrad, Bulgaria we demonstrated that Bulgarian hot springs harbor rich archaeal diversity (14). here we report the molecular characterization of biodiversity of archaeal community in Vlasa hot spring located in the same region, by two parallel analyses, 16S rRnA analysis and assessment of diversity of Glycoside hydrolases family 4 (Gh4) gene.…”
Section: Introductionmentioning
confidence: 99%